Peran Bayt Al-Qur'an & Museum Istiqlal bagi Pembangunan Bangsa Indonesia - Uka Tjandrasasmita (SUHUF, 2008)
Museum is a place where collections are stored for the purposes of research, study and recreation. Bayt Al-Qur 'an & Museum Istiqlal is a government institution under the authority of the Ministry of Religious Affairs of the Republic of Indonesia managing the manuscripts (mushaf) either new or ancient ones, as well as other Islamic heritage materials. It is hoped that this institution will be able to play its role in collecting the materials, in preserving its materials as well as in making the network to invite as many visitors as possible. It is for this reason that the socialization can be done through the activities such as MTQ (the contest of the art of reading the Holy Qur'an), publication and cooperation with other departments.